Productive potential and castor bean selection of the FCA-PB cultivar progenies1 - Silva, Jackson Da; Ramos, Andréia Rodrigues [UNESP]; Amorim, Deoclécio Jardim [UNESP]; Zanotto, Mauricio Dutra [UNESP]; Sartori, Maria Márcia Pereira [UNESP] (Universidade Federal de Viçosa, 2020)
Castor bean is a very important crop, however, in Brazil it still has relatively low productivity, 0.47 Mg ha-1 as a mean. Besides that the Country has significant castor oil demand and depends on international commerce to complement its production. The solution of these problems goes through the development of genotypes highly productive and adapted to the producing regions. So, the objective of this research was to evaluate the productive potential and selection of castor progenies of the cultivar FCA-PB, resulting from three types of pollination, in two crops and in two localities of the State of São Paulo. Grain productivity was evaluated, and some genetic parameters were estimated. In relation to the 2005/2006 crop, the progeny 49 cultivated in the locality of São Manuel produced 4170.66 kg ha-1 of grains. The highest heritability coefficients were observed in the 2005/2006 crop in the locality of Araçatuba. Progenies 1, 5, 6, 8, 15, 18, 19, 21, 27, 31, 35, 36, 38, 45, 49, 55, 56 and 58 were selected. Genotype interaction with the location indicated productive materials and adapted to the state of São Paulo.
Keywords: Ricinus communis L.; breeding; pure lines; stability.